2013
DOI: 10.1016/j.msea.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Toughening mechanism for Ni–Cr–B–Si–C laser deposited coatings

Abstract: Laser deposited coatings were made from Colmonoy 69 Ni-Cr-B-Si-C alloy and Nb-modified Colmonoy 69 using laser cladding with powder injection. Addition of Nb was done to decrease the structural scale of Cr boride precipitates by providing Nb-rich nucleation agents. The purpose of the study was to evaluate the viability of microstructural refinement as a toughening mechanism for Ni-Cr-B-Si-C alloys. The results show that although a significant refinement of the Cr-rich precipitates while preserving the original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The value of dilution ratio of the coating was calculated as nearly 50%, so the transition zirconium element diffusing in the molten pool reacted with other alloying elements and it can be predicted that a large number of Zr-containing compounds were formed Previous works by I. Hemmati [20,29] shown that hardfacing Ni-Cr-B-Si alloy had a tendency to form multiple microstructures. In this study, the same coating exhibits various microstructures along the depth of the deposit.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The value of dilution ratio of the coating was calculated as nearly 50%, so the transition zirconium element diffusing in the molten pool reacted with other alloying elements and it can be predicted that a large number of Zr-containing compounds were formed Previous works by I. Hemmati [20,29] shown that hardfacing Ni-Cr-B-Si alloy had a tendency to form multiple microstructures. In this study, the same coating exhibits various microstructures along the depth of the deposit.…”
Section: Resultsmentioning
confidence: 99%
“…One of reasons for such tendency discussed in Ref. [20] was that Ni-Cr-B-Si alloy had a large solidification range, and it is possible to follow a variety of solidification paths at different cooling rates. Moreover, the melting of some zirconium substrate near the interface and the effect of Marangoni movement [30,31] both resulted in the nonuniform distribution of elements in the molten pool.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In consideration of Ni-Zr intermetallic compounds and Zr-Si ceramics exhibiting higher hardness than most zirconium alloys and that Ni-Cr-B-Si alloy is a kind of conventional cladding powder [43], Ni-Cr-B-Si alloying powder was selected to be laser cladded on zirconium alloy. The aim of present work is to in situ synthesize Ni-Zr intermetallics/Zr-Si ceramics reinforced composite coatings on zirconium alloy by high power diode laser, reveal phase constituents and microstructural evolution and evaluate the wear resistance of coatings.…”
Section: Introductionmentioning
confidence: 99%